Analysis of Process‐Related Quality Metrics and Survival of Patients with Oral Cavity Squamous Cell Carcinoma. (7th May 2019) - Appachi, Swathi; Shah, Janki; Reddy, Chandana; Bowen, Andrew; Koyfman, Shlomo; Lamarre, Eric
Abstract : Objective: To analyze the association of prior reported key quality metrics—neck dissection ≥18 nodes, radiation oncology referral for stage III/IV disease, unplanned surgery ≤14 days, and unplanned readmission ≤30 days—with disease‐free survival (DFS) and overall survival (OS) in oral cavity cancer (OCC). Study Design: A retrospective chart review. Setting: A tertiary care center from 1995 to 2016. Subjects and Methods: Data from patients with OCC who underwent primary surgery were studied. The association of quality metrics and pathology with DFS/OS was determined by Cox proportional hazards regression analysis. Results: A total of 514 patients were included, and 398 (77.4%) underwent elective neck dissection. Key metrics were not associated with DFS on analysis, but higher pathologic stage and extracapsular extension (ECE) were. When stratified by stage, unplanned readmission within 30 days was associated with decreased survival on multivariate analysis (HR = 0.40; 95% CI, 0.20‐0.85; P =. 02) for patients with clinical stage III or IV disease. ECE was associated with decreased survival among these patients as well. Neck dissection with ≤18 nodes (HR = 0.62; 95% CI, 0.44‐0.86; P =. 004) and unplanned surgery within 14 days (HR = 0.56; 95% CI, 0.32‐0.96; P =. 03) were associated with decreased survival on univariate analysis but not on multivariate analysis. ECE and higher‐stage disease were associated with decreased OS on multivariate analysis. Conclusion: In this study, aggressive pathology, rather than adherence to key quality metrics, was associated with lower DFS and OS among patients with OCC. More studies are needed to elucidate the association of quality metrics with survival.